The Tulong Dunong Program: A Literature Review Addressing Challenges in Supporting Filipino Students - Maroma, Dolly P.; Maroma, Allen N. (ASEAN Journal of Community Engagement, 2025)
This article evaluates the opportunities and challenges of the Tulong Dunong Program (TDP), a government-sponsored program that seeks to provide access to education for disadvantaged Filipino learners in the Philippines. The research tackles contextual literature, from international to local, on how far TDP has expanded education access, an offshoot of which has decreased the dropout rate and increased socio-economic mobility. This research employs a systematic literature review to analyze the impact and challenges of the TDP of the Philippines. The dominant thematic categories that emerged were the positive effect of financial assistance on performance and retention, the importance of financial literacy to gain from the program, and hindrances such as delayed payment, insufficient funding, and bureaucratic inefficiency. Based on the review, it is shown how the TDP has managed to even the playing field in terms of providing access to tertiary education to various marginalized groups by eliminating cost as a limiting factor; there still exist, however, barriers that need to be addressed so that the TDP can realize its vision. The recommended policy interventions include augmented funding, simplification of application procedures, enhanced outreach activities, implementation of sound monitoring and evaluation systems, and inclusion of financial literacy training. These will help promote better implementation of the program and ensure that it continues to provide equitable opportunities to Filipino students, as a part of community empowerment and national development. According to the findings of the study, the TDP turned out to be one of the best instruments of the Philippine government in democratizing higher education toward inclusive development for the communities, notwithstanding its weaknesses.